Administrative Support and its Effectiveness on Teachers’ Professional Contentment and Retention - C. Po, Genevive Ann; Ramirez, Cybill Ann A. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study examined the effectiveness of administrative support and its relationship with teachers’ professional contentment and retention in rural public elementary schools in Calatrava District I. This addresses the lack of empirical research focusing on rural school settings. Specifically, it assessed administrative support in terms of professional development opportunities, workload management, and stress reduction interventions; teachers’ professional contentment in terms of overall satisfaction, well-being, and motivation; and teacher retention as reflected in the intention to stay and commitment to the school. The study also considered recent Department of Education policies, such as the removal of non-teaching administrative tasks, and was aligned with the United Nations Sustainable Development Goals, specifically SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth). A quantitative correlational research design was employed. Data were collected from 160 teachers selected through stratified random sampling from 22 schools using a validated self-made questionnaire. Descriptive and inferential statistics were used for the data analysis. The results revealed that administrative support, teachers’ professional contentment, and teacher retention were rated as Very High. Significant positive relationships were found between administrative support and both teachers’ professional contentment and retention rates. These findings indicate that strong administrative support systems contribute to improved teacher satisfaction, well-being, motivation, and long-term commitment in rural settings. Based on the findings, a Faculty Development Plan was proposed to strengthen administrative practices related to professional development, workload management, and stress reduction interventions. The plan serves as a practical guide for school administrators to promote teacher growth, workplace well-being, and organizational stability in rural schools.